Field testing a conceptual framework for innovation platform impact assessment: The case of MilkIT dairy platforms in Tanga region, Tanzania - Pham Ngoc Diep; Cadilhon, Joseph J.; Maass, Brigitte L. (Informa UK Limited, 2015)
This article studies the impact of innovation platforms in Tanga Region, Tanzania, set up by the MilkIT dairy development project to intensify smallholder production through feed enhancement and value chain approaches. The conceptual framework used builds up from three socio-economic theories. The Structure-Conduct-Performance model of markets contributes its elegant assumption, linking the way markets are organized with how market actors behave, which has an influence on market performance. The framework is transposed to study innovation platforms, which can be envisaged as market-enhancing institutions, according to New Institutional Economics, the second theory also contributing notions of transaction costs to the framework. The final theoretical contribution comes from business relationship marketing with its field-tested constructs for supply chain performance. This new conceptual framework applied to innovation platforms posits that the structure of the platform (how it is organized) has an impact on its members’ conduct (how they communicate and share information), which in turn influences platform performance targeted by members (feed availability and accessibility). Empirical data were collected from stakeholders involved in the MilkIT platforms through focus group discussions, key informant interviews and a survey of 121 farmers. Data were analysed using principal components factor analysis followed by regression analysis. This study finds positive links between frequency, quality and modes of communication by livestock keepers with their perception of satisfactory feed availability and accessibility. On the other hand, results for members and non-members of the platform are not statistically significantly different, probably due to the very early stage of platform development.